Disharmonisasi Konsep Hukum Dalam Undang-Undang Administrasi Pemerintahan di Indonesia - Mufidah, Nuruz Zakiyatul (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
Regularity and suitability between legislations and concepts of law are commonly used very important. that's aim to ensure certainty of law. regularity and stability are called harmonization in law. The law Number 30/2014 about administrative Governance is the first law for the management of decision-making and/or actions for government officials and/or government bodies in the Indonesian government. The People's Representative Council takes 10 years to draft a law about governance administration. So, The drafting of this law should have no gaps. the drafting harmonizes with other legislations and commonly used legal concepts in Indonesian law. Therefore, it is necessary to do legal research using a statute approach and a conceptual approach. The aim of this research is so that the research results can be used to revise administrative law in the future. As A result of this research, many concepts in the administration government of law are not harmonized with other legislations and commonly used legal concepts. Firstly, administrative law concepts, secondly Court concepts, thirdly government concepts, fourthly disharmonization concepts of administration decree, and fifthly disharmonization of legal forming princips, sixty disharmonization concession concepts and then the drafting does not harmonize between norm and implementation.